Psychometric properties of Lock-Wallace short marital adjustment scale (LWSMAT) for Bangladeshi couples - Khatun, Mosammat Nazma; Deeba, Farah; Tushar, Tanzir Ahmmad (Dhaka University Journal of Biological Sciences, 2019)
The present study aimed to explore psychometric properties of the Lock- Wallace Short Marital Adjustment Scale to use in the context of Bangladesh. The original scale consisted of 15 items and higher scores on the scale indicate greater marital satisfaction. After attaining agreement on the appropriateness of translated items by judges, item analysis was done using 318 clinical and nonclinical samples. The Cronbach’s Alpha and split-half reliability of the adapted scale was 0.92 and 0.95, respectively. The test-retest correlation was also found to be significant (r = 0.95, α = 0.01). Construct validity was measured by computing discriminant validity (F = 38.88, α < 0.001) between the clinical and non-clinical sample. Convergent validity was also ensured by measuring correlation(r = 0.72, α = 0.01) between Lock-Wallace scale and Spanier's Dyadic Adjustment Scale. It is suggested that the scale be used in Bangladeshi context considering that the item may incur low score for couples. Dhaka Univ. J. Biol. Sci. 28(2): 159-165, 2019 (July)